The Elephant in the Room: On the Absence of Corporations in Bernard Hodgson’s Economics as a Moral Science - Bishop, John Douglas (2012)
In his book Economics as a Moral Science, Bernard Hodgson argues that economics is not value neutral as is often claimed, but is a value-laden discipline. In the long argument for this in his book, Hodgson never discusses or even mentions corporations. This article explains that corporations are absent from Hodgson’s discussion because he considers only the consumption side of general equilibrium theory (GET), and it shows that if Hodgson had included corporations and the production side, his overall argument would have been more complete and convincing. This article shows that Hodgson’s methodology, when applied to the production side of GET, has value implications for CEOs of large corporations, for shareholders and members of Boards of Directors, and for legislators and regulators of business. Hodgson’s claim that economics must consider the ability of economic agents to create or change the institutional, cultural, and organizational conditions of their own economic actions is supported and expanded.
Keywords: Rationality; Neo-classical economics; Moral science; stockholder theory; Economic Theory; Corporations; Value-laden economics